Knowledge is power? Cervical cancer prevention in female OB/GYNs compared to other female physicians - Gal Hershkovitz; Gal Hershkovitz; Yifat Ochshorn; Yifat Ochshorn; Nadav Michaan; Nadav Michaan; Elisheva Fiszer; Elisheva Fiszer; Dan Grisaru; Dan Grisaru; Yael Raz; Yael Raz (Frontiers in Public Health, 2023)
Cervical cancer (CC) screening and prevention are crucial responsibilities of obstetrician-gynecologists (OB/GYNs). Our study aimed to investigate whether knowledge impacts OB/GYNs’ (n = 42) adherence to CC prevention measures by comparing them to non-OB/GYN physicians (n = 80). An anonymous questionnaire collected demographic information, personal screening habits and evaluated their knowledge of CC prevention. Results revealed that OB/GYNs exhibited superior knowledge of CC risk factors and prevention compared to non-OB/GYNs. Of note, a lower percentage of OB/GYN residents correctly identified the recommended upper age limit for cervical screening and for HPV vaccination compared to attending OB/GYNs (50% vs. 83%, p = 0.04 and 11% vs. 50%, p = 0.01, respectively). Despite these findings, most physicians from both groups recommended HPV vaccination. Cervical screening rates were similar between OB/GYNs and non-OB/GYNs (75% vs. 83%, p = 0.3). Half of OB/GYNs initiated their own cervical screening, similar to non-OB/GYNs. Interestingly, residents had higher HPV vaccination rates compared to attending physicians, irrespective of specialty (OB/GYNs – 38.89% vs. 4.76%, p = 0.0149; non-OB/GYNs – 51.06% vs. 15.38%, p = 0.0028). In conclusion, contrary to the assumption that physicians prioritize personal well-being, our study reveals the opposite. While skilled in guiding patients through CC screening and prevention, female OB/GYNs often neglect their own health. OB/GYNs must also be educated and supported in safeguarding their health, setting an essential example for patients.